2021
DOI: 10.1186/s13244-021-01024-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of uncommon prostate diseases: combining mpMRI and clinical information

Abstract: The differential diagnosis of abnormalities in the prostate is broad, covering common (acinar adenocarcinoma, benign prostatic hyperplasia, chronic prostatitis, hemorrhage, cysts, calcifications, atrophy and fibrosis) and less common conditions (tumors other than acinar adenocarcinoma, granulomatous prostatitis containing tuberculosis, abscesses and other conditions, and idiopathic disorders such as amyloidosis and exophytic benign prostatic hyperplasia). Recent advances in magnetic resonance imaging (MRI) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 65 publications
0
18
0
4
Order By: Relevance
“…PSA is a glycoprotein that is produced by the secretory epithelium of the prostate gland and it has been reported to be mildly increased in BPH. 46 PSA level will significantly increase in both benign and malignant lesions of the prostate but is usually marked in case of prostatic cancer. 47 , 48 Thus, the enhanced serum PSA levels of the disease control group suggest the development of BPH for this group of rats and a decrease in PSA is linked to a reduction in prostatic hyperplasia due to inhibition of prostatic 5α-reductase, the enzyme that converts DHT.…”
Section: Discussionmentioning
confidence: 99%
“…PSA is a glycoprotein that is produced by the secretory epithelium of the prostate gland and it has been reported to be mildly increased in BPH. 46 PSA level will significantly increase in both benign and malignant lesions of the prostate but is usually marked in case of prostatic cancer. 47 , 48 Thus, the enhanced serum PSA levels of the disease control group suggest the development of BPH for this group of rats and a decrease in PSA is linked to a reduction in prostatic hyperplasia due to inhibition of prostatic 5α-reductase, the enzyme that converts DHT.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging observations showed that most of the prostate cancer was convex, while most of the prostate inflammatory diseases were capsular atrophy and gland collapse. Prostate cancer is mostly unilateral lesions with focal nodular low signal, clear boundary and mass effect, which often leads to destruction of the prostate capsule [ 14 , 15 ]. We calculated the oval area as its "ideal prostate area" by measuring the transverse and longitudinal diameters of the prostate, and calculated the DPC compared to its true area.…”
Section: Discussionmentioning
confidence: 99%
“…Benign prostatic hyperplasia (BPH), a pathology for which lower urinary tract symptoms are common manifestations, affects more than half of men above 65 years old 1 . Although Prostate cancer occurs independently of benign prostatic hyperplasia, there might be some overlapping in symptoms, biomarker expression, or secretion 5 . Prostate cancers are most often detected based on elevated blood levels of prostate‐specific antigen, a glycoprotein (PSA > 4 ng/mL) generally expressed by prostate tissue, 3 and nonspecific lower urinary tract symptoms 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancers are most often detected based on elevated blood levels of prostate‐specific antigen, a glycoprotein (PSA > 4 ng/mL) generally expressed by prostate tissue, 3 and nonspecific lower urinary tract symptoms 6 . Also, common prostate diseases, including BPH, and prostatitis, have varying degrees of elevated blood PSA levels and nonspecific lower urinary tract symptoms (LUTS) 5,6 . Therefore, a tissue biopsy is a gold standard for confirming prostate cancer and defining the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%